Aspergillus Flavus, Aspergillus Niger, and Aspergillus Terreus are Three Distinct Types of Fungi Used Utilized in Crude Oil Biodegradation: Aspergillus Flavus, Aspergillus Niger, dan Aspergillus Terreus adalah Tiga Jenis Jamur yang Digunakan untuk Biodegradasi Minyak Mentah - AL-Shemary, Ahmed J.; AL-Jabberi, Meiad M.; AL-Saad, Hamid T. (Indonesian Journal on Health Science and Medicine, 2024)
The biodegradation process is one of the best ways to remove organic pollutants with different organic concentrations that have a very dangerous impact on the ecosystem. Soil samples contaminated with crude oil were collected from eight oil producing sites of Basrah Governorate. In the present study three types of fungi species were isolated from the soil contaminated with crude oil in the producing fileds .The fungi species were diagnosis of in the laboratories of the College of Science / University of Basrah to identify them accurately. as Aspergillus flavus , Aspergilus niger and Aspergillus terreus ltheir ability to biodegrade crude oil was tested of the mineral salts medium. As single isolated for 10 , 20 and 30 days incubation. results showed that the Aspergillus flavus the best with biodegradation ability at different incubation periods. Highlights: Biodegradation effectively removes harmful organic pollutants from ecosystems. Crude-oil-contaminated soils in Basrah revealed three fungi species: Aspergillus flavus, niger, terreus. Aspergillus flavus showed superior crude oil degradation over 10–30 days incubation.. Keywords: crude oil concentrations, fungi and biodegradation.